Konsolidacja obszarów działalności bankowej i ubezpieczeniowej po wejściu Polski do Unii Europejskiej a możliwość funkcjonowania "organizacji bancassurance" na rynku finansowej obsługi jednostek samorządu terytorialnego - Kociemska, Hanna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
This article presents an idea and practical implications of the emerging banking and insurance sector in Poland. The author emphasizes the subject of servicing local governments by banks and insurance organizations. The paper discusses also the possibility of existence of bancassurance organizations on Polish financial market. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 386-399